The Correlation between Studentsâ Vocabulary Mastery and Their Reading of Narrative Text Ability - Alfiawati, Riska (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
The objective of this research was to know and describe the correlation between studentsâ vocabulary mastery and their reading ability of narrative text at the second semester of the tenth class at SMA Negeri I Pringsewu in 2015/2016. This research, the writer used descriptive quantitative method. The population in this research was the students at the second semester of the tenth class at SMA Negeri I Pringsewu in 2015/2016 consisting of 289 students in 9 classes. The sample of this research was X2 consisted of 31 students. In determining the sample, the writer used cluster random sampling technique. In data collecting technique, the writer used objective test in the form of multiple choice test consisting of 40 items test with 5 options A, B, C, D and E. In analyzing the data, the writer used Product Moment formula. The result of this research showed that the result of calculation by using Product Moment formula got rxy was 0.76. After consulting, the writer knew that 0.76 was taken place between 0.600 â 0.800 that showed that the correlation was high. Furthermore, rxy was consulted with rtable with significant 5% with N=31 was 0.355 so rxy was higher than rtable (0.76 > 0.355). It means that the writer proved that there is a significant correlation between studentsâ vocabulary mastery and their reading ability of narrative text at the second semester of the tenth class at SMA Negeri I Pringsewu in 2015/2016.